Analysis of Purified Pancreatic Islet Beta and Alpha Cell Transcriptomes Reveals 11β-Hydroxysteroid Dehydrogenase (Hsd11b1) as a Novel Disallowed Gene - Pullen, Timothy J.; Huising, Mark O.; Rutter, Guy A. (Frontiers in Genetics, 2017)
We and others have previously identified a group of genes, dubbed “disallowed”, whose expression is markedly lower in pancreatic islets than in other mammalian cell types. Forced mis-expression of several members of this family leads to defective insulin secretion, demonstrating the likely importance of disallowance for normal beta cell function. Up to now, transcriptomic comparisons have been based solely on data from whole islets. This raises the possibilities that (a) there may be important differences in the degree of disallowance of family members between beta and other either neuroendocrine cells; (b) beta (or alpha) cell disallowed genes may have gone undetected. To address this issue, we survey here recent massive parallel sequencing (RNASeq) datasets from purified mouse and human islet cells. Our analysis reveals that the most strongly disallowed genes are similar in beta and alpha cells, with 11β-hydroxysteroid dehydrogenase (Hsd11b1) mRNA being essentially undetectable in both cell types. The analysis also reveals that several genes involved in cellular proliferation, including Yap1 and Igfbp4, and previously assumed to be disallowed in both beta and alpha cells, are selectively repressed only in the beta cell. The latter finding supports the view that beta cell growth is selectively restricted in adults, providing a mechanism to avoid excessive insulin production and the risk of hypoglycaemia. Approaches which increase the expression or activity of selected disallowed genes in the beta cell may provide the basis for novel regenerative therapies in type 2 diabetes.□